Brick kilns and agricultural productivity in Bangladesh: Evidence from satellite data and a natural experiment - Mahzab, Moogdho; Bakhtiar, M. Mehrab; Mattsson, Martin; Anowar, Md Sadat (International Food Policy Research Institute, 2025)
Bangladesh’s brick kiln industry plays a critical role in supplying construction materials for rapid urbanization. However, the sector remains largely informal and weakly regulated, with widespread extraction of fertile topsoil and substantial emissions of particulate matter and black carbon. These practices raise growing concerns about long-term environmental degradation, agricultural productivity, and food security.